Strategi Guru Taman Pendidikan Al- Qur’an (TPQ) Al-Mujahadah Dalam Mengatasi Kejenuhan Belajar Membaca Alqur’an Pada Anak di Dusun Sepinggan Gelik - Siti Zulaiha; Ubabbudin; Mauizatul Hasanah (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
This study stems from the strategies used by teachers of the Al-Qur'an Education Park in Overcoming the Boredom of Learning to Read the Qur'an of Children in Sepinggan Gelik Hamlet, Semparuk District in 2023. This study aims, 1) to describe and analyze the implementation of learning at the Al-Mujahadah Al-Qur'an Education Park (TPQ) in overcoming the boredom of learning to read the Qur'an in children in Sepinggan Gelik Hamlet, Semparuk District 2023. 2) to know what are the supporting and inhibiting factors in the implementation of learning Taman Pendidikan Al-Qur'an (TPQ) Al-Mujahadah in overcoming boredom in learning to read the Qur'an in children in Sepinggan Gelik Hamlet, Semparuk Subdistrict. This research uses a qualitative approach. The research subjects were two teachers of the Al-Qur'an education park and 2 students. Data collection techniques in this study are: Observation, Interview, and Documentation. While data analysis techniques used data reduction, data presentation, verification and conclusion drawing. The results of the study are: a) Al-Mujahadah Quranic Education Park is held on Monday, Wednesday, and Thursday at 15.00-16.45. b) congregational asar prayer, prayer and roll call c) children write Al-Qur'an verses and draw. d) rest e) material f) prayer. The supporting factor for the implementation of this learning is the discussion and cooperation between the Al-Qur'an education park teachers and the mosque administrators and the community. Second, the inhibiting factors in the implementation of the Al-Qur'an Education Park are the lack of response from children so that it is rather difficult to apply the strategies to be used, and the large amount of arrears in dues from students, as well as teachers lacking mastery of technology so it is difficult to find references via the internet.